Developing echolocation: distinctive patterns in the ontogeny of the tympanoperiotic complex in baleen and toothed whales (Cetacea). (28th December 2021) - Lanzetti, Agnese; Chrouch, Natasha; Portela Miguez, Roberto; Fernandez, Vincent; Goswami, Anjali
Abstract: Cetaceans (baleen and toothed whales) present a unique set of adaptations for life in water. Among other abilities, the two living groups can hear and produce different sound frequencies: baleen whales use low frequencies primarily for communication, whereas toothed whales acquired the ability to echolocate using high-frequency sounds. Both groups exhibit modifications to the morphology of the ear bones (tympanic bulla and periotic) that closely track their behaviour and ecology. The evolution of sound reception in whales is being investigated thoroughly, whereas the changes in prenatal development (ontogeny) that generate these disparate ear bone morphologies remain mostly unknown. In this study, we characterize the ontogeny of the ear bones in Cetacea by looking at the progression of ossification and associated changes in morphology using a combination of traditional measurements and an innovative landmark-free method to quantify shape on a newly assembled three-dimensional dataset spanning the ontogeny and phylogeny of extant Cetacea. We have found that the two groups of Cetacea share some aspects of ear ontogeny, such as a common growth trajectory of the periotic. However, differences in ossification, allometry and growth trajectory, particularly in the periotic bone, reflect their divergent inner ear morphology and hearing abilities.